Pengaruh Pengembangan Karir, Kepuasan Kerja Dan Komitmen Organisasi Terhadap Intensi Turnover Karyawan Di Kawasan Industri MM2100 - Hasyim, Wachid; Jayantika, Lestari Ayu (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2021)
This study aims to determine the effect of Career Development, Job Satisfaction and Organizational Commitment on Employee Turnover Intentions. the method used in this study using quantitative methods. The sample in this study were employees who worked in the MM2100 Industrial Estate with as many as 100 people. Statistical analysis performed included multiple linear regression and hypothesis testing. Based on the results of data analysis, it can be concluded that: There is a negative and significant effect of Career Development on Employee Turnover Intentions. There is a negative and significant effect of job satisfaction on employee turnover intentions. There is a negative and significant effect of organizational commitment on turnover intentions. The value of the coefficient of determination is 0.820, which means that variations in employee turnover intentions in the MM2100 Industrial Estate are influenced by Career Development, Job Satisfaction and Organizational Commitment by 82%. While the remaining 18% is influenced by other variables outside the study.